Influencing factors in dietary supplement consumption among university students / Nor Intan Shamimi Abdul Aziz - Abdul Aziz, Nor Intan Shamimi; Mohamed Shafii, Nurul Fazira; Azizam, Nor Azmaniza; Dzulkiply, Mohd Redhuan (Universiti Teknologi Mara Selangor, 2020)
In recent years, there has been an increasing interest in consuming dietary supplements which believed to promote a healthy lifestyle among generations. However, lack of knowledge and peer pressure can be the problems despite its long success. Thus, the aim of this study is twofold; i) to assess the sociodemographic information among the students on taking dietary supplements and ii) to examine the influencing factors that lead to dietary supplements consumption among undergraduate students in Selangor, Malaysia. Findings explained through equal distribution of survey between faculties, a majority of female students (72.5%) participated in this study compared to male students (27.5%) with both genders are in a good health condition (60.6%) and having normal BMI reading (65.3%). All the factors such as the perception of knowledge (r = 0.387), lifestyle behaviour (r = 0.541) and efficacy of the supplements (r = 0.548) indicate a moderate positive relationship towards dietary consumption in their daily life, respectively. More health educational talks need to be conducted in future to increase knowledge among university students. Future recommendations are drawn through the suggestion of reassessing other factors that lead to the DS consumption through qualitative method analysis.